Hubungan Terapi Akupunktur Dengan Tingkat Kepuasan Dan Penurunan Nyeri Bahu - Atika Afniratri; Mehdya Vikia Murti; Fathin Nafisyah (Public Health Journal, 2026)
Shoulder pain is one of the most common musculoskeletal disorders encountered in clinical practice, with impacts including limited joint movement, impaired daily activities, and decreased quality of life. Conventional therapies such as anti-inflammatory drugs and physiotherapy do not always provide satisfactory results; therefore, acupuncture therapy has increasingly been considered as a relatively safe alternative for managing shoulder pain with minimal side effects. This study aimed to determine the relationship between acupuncture therapy, patient satisfaction levels, and reductions in shoulder pain. This study used a quantitative approach with a descriptive correlational design and a cross-sectional design. The study sample consisted of 50 acupuncture patients at AAA Aceh Neuhun Clinic who were selected using consecutive sampling. Data were collected using a patient satisfaction questionnaire (Likert scale) and the Numeric Rating Scale (NRS) to measure pain before and after therapy. Data were analyzed using the Wilcoxon test and Spearman's rho correlation test. The results showed that the majority of respondents experienced a large reduction in shoulder pain (46.0%) and had a fairly satisfied level of satisfaction (50.0%). The Wilcoxon test showed a significant difference between pain before and after acupuncture therapy (p = 0.000), indicating that acupuncture therapy was effective in reducing shoulder pain. The Spearman's rho correlation test showed a strong and significant relationship between the number of therapy sessions and patient satisfaction (r = 0.554; p = 0.000), as well as a strong and significant relationship between the reduction in shoulder pain and patient satisfaction (r = 0.780; p = 0.000). It can be concluded that acupuncture therapy has a significant relationship with the reduction of shoulder pain and increased patient satisfaction. The results of this study are expected to serve as a basis for consideration by healthcare facilities in optimizing acupuncture services as an alternative approach to managing shoulder pain.